2010
DOI: 10.2353/ajpath.2010.091183
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Induces Smad3-Dependent β1 Integrin Gene Expression in Epithelial-to-Mesenchymal Transition during Chronic Tubulointerstitial Fibrosis

Abstract: Transforming growth factor-␤1 (TGF-␤1)-induced epithelial-to-mesenchymal transition (EMT) contributes to the pathophysiological development of kidney fibrosis. Although it was reported that TGF-␤1 enhances ␤ 1 integrin levels in NMuMG cells , the detailed molecular mechanisms underlying TGF-␤1-induced ␤ 1 integrin gene expression and the role of ␤ 1 integrin during EMT in the renal system are still unclear. In this study , we examined the role of ␤ 1 integrin in TGF-␤1-induced EMT both in vitro and in vivo. TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
98
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 51 publications
5
98
0
4
Order By: Relevance
“…Currently, TGF-β1 is recognized as one of the key factors in the formation and progression of interstitial fibrosis. It may induce renal tubular epithelial cell apoptosis, transdifferentiation of tubular epithelial cells into myofibroblasts (MFB), as well as excessive concentration of the ECM proteins, and eventually lead to interstitial fibrosis (24)(25)(26). The present study observed a significant increase in TGF-β1, Col-I and α-SMA expression levels in nephridial tissue, as well as interstitial fibrosis in the UUO group of rats.…”
Section: Discussionsupporting
confidence: 56%
“…Currently, TGF-β1 is recognized as one of the key factors in the formation and progression of interstitial fibrosis. It may induce renal tubular epithelial cell apoptosis, transdifferentiation of tubular epithelial cells into myofibroblasts (MFB), as well as excessive concentration of the ECM proteins, and eventually lead to interstitial fibrosis (24)(25)(26). The present study observed a significant increase in TGF-β1, Col-I and α-SMA expression levels in nephridial tissue, as well as interstitial fibrosis in the UUO group of rats.…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, acinar cells, which we find to express low levels of β1 integrin, are unable to undergo significant proliferation unless they enter an acinar-to-ductal transdifferentiation (Fukuda et al, 2012;Kopp et al, 2012;Reichert et al, 2013). Islet cells have been reported to undergo epithelial-tomesenchymal transition when replicating (Kaido et al, 2010;Montgomery and Yebra, 2011), a phenomenon that has been described in many epithelial cell types and that is associated with significant upregulation of β1 integrin (Lim and Thiery, 2012;Yeh et al, 2010). This provides a possible mechanism by which cells about to enter the cell cycle can enhance their propensity to use this integrin subunit to respond to microenvironmental cues and activate pro-proliferative signaling cascades.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies in cells from the proximal tubule have demonstrated that angiotensin II-induced tubular EMT was SMAD3-dependent [44]. Similarly, (β)1-integrin gene expression, a potential therapeutic target for renal fibrosis, is also upregulated in unilateral obstruction and in chronic tubulointerstitial fibrosis via a SMAD3-dependent mechanism [45]. However, despite the predominant involvement of SMAD3, a role for SMAD2 should not be discounted [46].…”
Section: Discussionmentioning
confidence: 99%